Strata Norma Dalam “Karya Cipta Puisi Anak” Karya Murid SDN Banyudono 2 - Amalia, Liza Rizqi; Qomariyah, U'um (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Research on children's literature is still rare because children's literature is not given enough attention. Whereas through children's literature it can increase children's imagination which affects the development of children's abilities. The purpose of this study is to analyze five poems by elementary school children using Roman Ingarden's norm strata approach. This research uses descriptive qualitative method with text analysis. The data source is the poetry collection book "Karya Cipta Puisi Anak" by students of SDN Banyudono 2. The results show that although children's poetry is simple, it still has various layers or norm strata that can be explored. Many children's poems use regular rhymes and themes of residence, natural beauty, or family. The objects used in the poems are also close to children so that the phenomena created are also about life in a child's perspective. Some children's poems can also be further researched for their meaning.